PROBLEMS OF MASTER'S DEGREE TRAINING IN ECONOMICS - Oleg V. Motovilov (Высшее образование в России)
The author proposes a number of ideas relating to MA training in economics. The paper considers the situation where in one audience meet the students with different levels of training including those who enter economic master's degree courses but do not have basic economic education. The responsibility for the implementation of the proposed solutions of this problem lies both with the university and the teacher. The author analyzes the situation when the state examination board is formed entirely by the employers' representatives or by members of professional associations. A number of problems that may arise in this case are discussed in the paper.